Plant coverage is a potential ecological indicator for species diversity and aboveground biomass in semi-steppe rangelands. (October 2018) - Sanaei, Anvar; Ali, Arshad; Chahouki, Mohammad Ali Zare; Jafari, Mohammad
Graphical abstract: Highlights: Plant coverage and species richness or Shannon's diversity were dependent indicators for biomass. Plant coverage and species evenness were independent indicators for aboveground biomass. Disturbance intensity had strongest negative effect on plant coverage rather than diversity. Rotational grazing system is a suitable choice for high plant coverage, diversity and biomass. Enhancement of plant coverage is important for higher species diversity and biomass. Abstract: The relationships between species diversity and aboveground biomass remain highly debated in contemporary ecology. Here, we proposed the following three hypotheses by evaluating three different paths between species diversity indices (species richness, evenness, Shannon's species diversity, and a combination of species richness and evenness) and plant coverage for explaining variation in aboveground biomass, in addition to the influences of abiotic factors and disturbance intensities: 1) plant coverage increases species diversity through light capture and use in the vertical physical space; 2) species diversity increases plant coverage through species coexistence; and 3) species diversity and plant coverage may provide positive response to each other, and as a consequence enhance aboveground biomass in natural rangelands. We used structural equation models to explicitly test these hypotheses using biophysical data from 735 quadrats in semi-steppe rangelands in Iran. In all tested models, plant coverage possessed strongest positive effect on species richness and Shannon's species diversity but not on species evenness, and hence strongly determined aboveground biomass as compared to species diversity indices. Disturbance intensity decreased aboveground biomass directly and indirectly via plant coverage than that via species diversity, indicating that plant coverage is sensitive to disturbance intensities for driving aboveground biomass. Species richness or Shannon's diversity substantially enhanced aboveground biomass indirectly via plant coverage, indicating that plant coverage is a linking mechanism for the positive relationships between biodiversity and aboveground biomass. Practically, this study suggests that rotational grazing system might be a suitable choice for the enhancement of plant coverage and aboveground biomass while conserving biodiversity. Theoretically, this study suggests that plant coverage is a sustainable ecological indicator or linking mechanism for high species diversity and aboveground biomass in studied rangelands and other ecosystems in general.